Perturbation-Iteration Method for First-Order Differential Equations and Systems - Mehmet Şenol; İhsan Timuçin Dolapçı; Yiğit Aksoy; Mehmet Pakdemirli (Abstract and Applied Analysis)
The previously developed new perturbation-iteration algorithm has been applied to differential equation systems for the first time. The iteration algorithm for systems is developed first. The algorithm is tested for a single equation, coupled two equations, and coupled three equations. Solutions are compared with those of variational iteration method and numerical solutions, and a good agreement is found. The method can be applied to differential equation systems with success.